Organizational generativity the appreciative inquiry summit and a scholarship of transformation - Cooperrider, David L. (Bingley, U.K. : Emerald, 2013)
Appreciative Inquiry has touched and inspired the work of thousands who apply its development principles in a wide range of settings including industry, government, spiritual and not-for-profit organizations. The Advances in Appreciative Inquiry series facilitates an emergent dialogue within the social sciences and supports innovative and challenging scholarly work. It is dedicated to the advancement of Appreciative Inquiry as an approach to organizational and human development, and as an interdisciplinary, non-deficit theory of positive change processes in human systems. Guided by the ethos of Appreciative Inquiry, the book series supports an ongoing, distributed inquiry into the true, the good, the better and the possible. It is dedicated to advancing a "scholarship of the positive" and "positive scholarship." This volume aims to push the frontiers and solicit new tools and insights for expanding the state-of-the-art applications of Appreciative Inquiry. It revolves around three fundamental aspects of organizational generativity, namely: generative knowledge and organizational life, collective action and the appreciative inquiry summit, and sustainable inter-generative dynamics.
A contemporary commentary on appreciative inquiry in organizational Life / David L. Cooperrider -- The process of generative inquiry / Danielle P. Zandee -- Generative process, generative outcome : the transformational potential of appreciative inquiry / Gervase R. Bushe -- The generative archetypes of idea work / Michel Avital, Wietske van Osch -- The generative potential of cynical conversations / David S. Bright ... [et al.] -- The language of change : generativity in dialogical processes / Rombout van den Nieuwenhof -- Transcending the polarity of light and shadow in appreciative inquiry : an appreciative exploration of practice / Pamela C. Johnson -- The spark, the flame, and the torch : the positive arc of systemic strengths in the appreciative inquiry design summit / David L. Cooperrider -- The exponential inquiry effect magnified : the new AI summit in a technologically connected world / Lindsey N. Godwin, Pascal Kaplan, Kristin Bodiford -- Strategic convening for generative impact : enabling systemic change in complex environments / David L. Cooperrider, Dave Sherman, Eric Woychik -- Collective actualization : an interpretation of Rogers' Necessary conditions for change / Tiffany Schroeder -- Ensuring generativity beyond the AI summit event : a practical guide for designing an AI summit and advancing post-summit momentum / Molly McGuigan, C.J. Murphy -- Exploring transformative innovation through a world inquiry / David S. Bright, Ronald E. Fry, David L. Cooperrider -- The generative diffusion of innovation / Bonnie A. Richley, David L. Cooperrider -- Generative mobilization : appreciative social movements / Brodie Boland -- The evolution of appreciative inquiry : a novel approach in the making / Ilma Barros-Pose -- Appreciative intelligence and generativity : a case study of Rocky Flats nuclear weapons facility cleanup / Tojo Thatchenkery, Irma Firbida -- The Macon miracle : the magic of intergenerational design for the future of education / Cheri Torres ... [et al.] -- Intergenerational appreciative inquiry : caring for the future together / Matthew Moehle, Marge Schiller.
Includes index.
Print version record
Keywords: Business & Economics -- Human Resources & Personnel Management; Business & Economics -- Management; Business & Economics -- Organizational Development; Organizational theory & behaviour; Business & management; Organizational change -- Management; Appreciative inquiry; Organizational effectiveness